2020
DOI: 10.1101/2020.07.17.20156513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale Multi-omic Analysis of COVID-19 Severity

Abstract: We performed RNA-Seq and high-resolution mass spectrometry on 128 blood samples from COVID-19 positive and negative patients with diverse disease severities. Over 17,000 transcripts, proteins, metabolites, and lipids were quantified and associated with clinical outcomes in a curated relational database, uniquely enabling systems analysis and cross-ome correlations to molecules and patient prognoses. We mapped 219 molecular features with high significance to COVID-19 status and severity, many involved in comple… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(108 citation statements)
references
References 103 publications
8
79
2
Order By: Relevance
“…Previously, we and others investigated the association of plasma and serum biomarkers with COVID-19 severity [7][8][9][10][11]14 . In other studies, the potential prognostic value of several established and newly discovered blood markers for predicting the future course of disease was investigated, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we and others investigated the association of plasma and serum biomarkers with COVID-19 severity [7][8][9][10][11]14 . In other studies, the potential prognostic value of several established and newly discovered blood markers for predicting the future course of disease was investigated, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent investigations have identified protein biomarkers and clinical parameters that classify COVID-19 patients according to disease severity [7][8][9][10][11][12][13][14][15] . To identify i) which of these markers and parameters correlate with each other by being attributed to a common biological or physiological response, and ii) which markers predict outcome, we longitudinally phenotyped 139 individuals admitted at Charité University Hospital, Berlin, Germany, between March 01, 2020 and June 30, 2020 due to PCR confirmed SARS-CoV-2 infection (Supp.…”
Section: Covariation Of Clinical Diagnostic Parameters and The Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, two recent studies that conducted an integrated immune analysis of COVID-19 patients found impaired IFN responses in severe and critically ill patients (Arunachalam et al, 2020;Hadjadj et al, 2020). Further support for the role of CoV-2 infection (Blanco-Melo et al, 2020;Emanuel et al, 2020;Overmyer et al, 2020;Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Gene expression data of SARS-CoV-2 infected individuals were analyzed using discovery (11 subjects with mild or severe SARS-CoV-2, single cell gene expression, GEO: GSE149689), validation (100 subjects, bulk cell RNA-seq gene expression, GEO Accession: GSE157103 6 ) and cellular source (7 subjects, single cell gene expression, GEO accession: GSE150728 7 ) cohorts. All analyses were performed in R software (version 4.0.2) 12 .…”
Section: Methodsmentioning
confidence: 99%